Methodological variation in headspace analysis of liquid samples using electronic nose - Knobloch, Henri; Turner, Claire; Spooner, Andrew; Chambers, Mark (Elsevier, 2009)
In past years, numerous electronic nose (e-nose) developments have been published describing analyses of solid-, liquid- or gaseous media in microbiological-, environmental-, agricultural- or medical applications. However, little has been reported about complex methodological pitfalls that might be associated with commercially available e-nose technology. In this paper, some of these pitfalls such as temperature, the use of filters and mass flow using different sampling methods (static- and dynamic sampling) are described for two generations of conducting polymer e-noses (ST114/214, CPs, both Scensive Tech. Ltd.). A comparison with metal oxide semiconducting field effect transistor/metal oxide semiconductor (MOSFET/MOS) e-noses regarding stability across replicates and over time was made. Changes in temperature were found to give larger sensor responses, whereas the application of filters led to quantitative and qualitative changes in sensor responses due to a change in mass flow which was also affected by the sampling method. Static sampling provided more stable flows across replicates. Variation was investigated for CPs and MOSFET/MOS e-noses that gave different responses over time and across replicates. These methodological factors cause a lack of stability and reproducibility, demonstrating the pitfalls of e-nose technology and therefore limit their utility for discriminating between samples.
Keywords: Electronic nose; Temperature effect; Headspace; Filter; Sampling method